How does differential rod contouring contribute to 3-dimensional correction and affect the bone-screw forces in adolescent idiopathic scoliosis instrumentation?. (November 2016) - Wang, Xiaoyu; Boyer, Laure; Le Naveaux, Franck; Schwend, Richard M.; Aubin, Carl-Eric
Abstract: Background: Differential rod contouring is used to achieve 3-dimensional correction in adolescent idiopathic scoliosis instrumentations. How vertebral rotation correction is correlated with the amount of differential rod contouring is still unknown; too aggressive differential rod contouring may increase the risk of bone-screw connection failure. The objective was to assess the 3-dimensional correction and bone-screw forces using various configurations of differential rod contouring. Methods: Computerized patient-specific biomechanical models of 10 AIS cases were used to simulate AIS instrumentations using various configurations of differential rod contouring. The tested concave/convex rod configurations were 5.5/5.5 and 6.0/5.5 mm diameter Cobalt-chrome rods with contouring angles of 35°/15°, 55°/15°, 75°/15°, and 85°/15°, respectively. 3-dimensional corrections and bone-screw forces were computed and analyzed. Findings: Increasing the difference between the concave and convex rod contouring angles from 25° to 60°, the apical vertebral rotation correction increased from 35% (SD 17%) to 68% (SD 24%), the coronal plane correction changed from 76% (SD 10%) to 72% (SD 12%), the thoracic kyphosis creation from 27% (SD 60%) to 144% (SD 132%), and screw pullout forces from 94 N (SD 68 N) to 252 N (SD 159 N). Increasing the concave rod diameter to 6 mm resulted in increased transverse and coronal plane corrections, higher thoracic kyphosis, and screw pullout forces. Interpretations: Increasing the concave rod contouring angle and diameter with respect to the convex rod improved the transverse plane correction but with significant increase of screw pullout forces and thoracic kyphosis. Rod contouring should be planned by also taking into account the 3-dimensional nature and stiffness of the curves and combined with osteotomy procedures, which remains to be studied. Highlights: Differential rod contouring was evaluated through numerical simulations of 10 scoliosis cases. Increasing differential rod contouring angle increased the transverse plane correction. Increasing rod diameter further improved transverse plane correction. Differential rod contouring increased screw pullout forces and thoracic kyphosis.